ANALYSIS OF THE NUTRITIONAL STATUS OF IAIN SALATIGA STUDENTS IN PHYSICAL EDUCATION LECTURES - Fatkhur Rozi (PHEDHERAL, 2021)
Nutritional status is a component that affects the level of health and fitness. The level of nutritional status is very important to monitor the condition. Nutritional status monitoring can be carried out during physical education learning because one of the learning objectives is to improve physical fitness and the level of nutritional status plays a role in it. Objective: Assessing the level of nutritional status of IAIN Salatiga students in physical education lectures. This study uses a quantitative method with a survey approach and is analyzed descriptively quantitatively. The population of this study was 127 students of IAIN Salatiga who attended physical education lectures. The sampling technique used is the Non Probability Sampling Technique with a census. The results were 10 severely underweight students, 22 underweight students, 75 normal students, 11 overweight students, and 9 obese students. Eight male students have normal status, 1 person is underweight, and 3 people are obese. Meanwhile, female students with normal status are 67 people, underweight are 21 people, severely underweight are 10 people, overweight are 11 people, and obese are 6 people. This study concludes that students of IAIN Salatiga who take physical education lectures generally have a normal nutritional status, but there are still some students who are severely underweight and obese who are at risk of disease.